In situ hybridisation: principles and applications - Looi, Lai Meng; Cheah, Phaik Leng (College of Pathologists, Academy of Medicine Malaysia, 1992)
In situ hybridisation (ISH) is based on the complementary pairing of labelled DNA or RNA probes with normal or abnormal nucleic acid sequences in intact chromosomes, cells or tissue sections. Compared with other molecular biology techniques applicable to anatomical pathology, ISH enjoys better rapport with histopathologists because of its similarity to immunohistochemistry. It has the unique advantage over other molecular biology techniques--largely based on probe hybridisation with nucleic acid extracted from homogenised tissue samples--of allowing localisation and visualisation of target nucleic acid sequences within morphologically identifiable cells or cellular structures. Probes for ISH may bear radioactive or non-radioactive labels. Isotopic probes (3H, 32P, 35S, 125I) are generally more sensitive than non-isotopic ones but are less stable, require longer processing times and stringent disposal methods. Numerous non-isotopic labels have been used; of these biotin and digoxigenin are the reporters of choice. Optimised non-isotopic systems of equivalent sensitivity to those which use radioactive-labelled probes have been described. In ISH, finding the optimal balance between good morphological preservation of cells and strong hybridisation signals is crucial. Tissue fixation and retention of cytoskeletal structures, unfortunately, impede diffusion of probes into tissues. ISH sensitivity is also influenced by inherent properties of the probe and hybridisation conditions. Although ISH is largely a research tool, it is already making strong inroads into diagnostic histopathology. It has been applied for the detection of various infective agents particularly CMV, HPV, HIV, JC virus, B19 parvovirus, HSV-1, EBV, HBV, hepatitis delta virus, Chlamydia trachomatis, salmonella and mycoplasma in tissue sections.(ABSTRACT TRUNCATED AT 250 WORDS)